Paced auditory serial addition test (PASAT): a very difficult test even for individuals with high intellectual capability - Joseph Bruno Bidin Brooks; Vinicius Oliveira Giraud; Youssef Jamal Saleh; Samuel Jose Rodrigues; Lucas Afonso Daia; Yara Dadalti Fragoso (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To assess the difficulty of paced auditory serial addition test (PASAT) in a population of high intellectual level, under ideal cognitive testing circumstances. METHOD: One hundred medical students underwent PASAT testing. They had slept well the night before, they had eaten before the assessment, they were not using any drugs that could affect the central nervous system and they did not have depression, anxiety or any chronic disease. RESULTS: The average result from the three-second version of PASAT was 57.5% and, from the two-second version, it was 44.3%. CONCLUSION: Even under ideal circumstances, PASAT is a very difficult test for the general population. It may not be ideal for neurologists to screen, assess and follow up patients with cognitive function in multiple sclerosis.